Patch test results in children and adolescents across Europe. Analysis of the ESSCA Network1 2002–2010. Issue 5 (5th June 2015) - Belloni Fortina, Anna; Cooper, Susan M.; Spiewak, Radoslaw; Fontana, Elena; Schnuch, Axel; Uter, Wolfgang; Aberer, Werner; Bircher, Andreas; Simon, Dagmar; Ballmer‐Weber, Barbara; Frosch, Peter; Fuchs, Thomas; et al.
Abstract Background Contact sensitization in children is more frequent than previously thought. Methods The ESSCA collected patch test data from 11 European countries aggregated to 4 European regions. Results Six thousand and eight patients aged 1–16 years old with suspected allergic contact dermatitis were analyzed during a period of 8 years (2002–2010). The overall prevalence of at least one positive reaction to a hapten was 36.9%. The 10 most frequent haptens were as follows: nickel sulfate, cobalt chloride and potassium dichromate, neomycin sulfate, Myroxylon pereirae resin (balsam of Peru), para‐phenylenediamine, chloromethylisothiazolinone/methylisothiazolinone 3:1, fragrance mix, lanolin alcohols, and colophony. No difference was found in the prevalence of at least one positive reaction to at least one hapten between boys and girls and between children with atopic dermatitis and children without. Children without atopic dermatitis, when compared with those with, had a significantly higher prevalence of contact sensitization for nickel sulfate (20.91% vs 16.87%, respectively), 4‐tert. butylphenol formaldehyde resin (1.61% vs. 0.7%), and para‐phenylenediamine (2.49% vs. 1.3%). Limitations of the study Chamber loading is not an exact science and variation may occur between staff and departments. Interinstitution variations in readings can occur. A possible geographic confounder is that the southern regions tested more children in the younger age group. Relevance was not addressed due to difficulties in the application of a set of uniform definitions. Conclusions Our study adds information on the most common contact allergens detected in children which could help to define a Standard European Pediatric Baseline Series.